The need for critical pedagogy and collabrative learning : a reflection on the educational systems of Uganda, Ghana, and the International Studies in Education Program (ISEP) at the University of Iceland - Emmanuel Mawuli Adom 1987-; Birungi Marion 1977- (2022)
The theory of critical pedagogy and collaborative learning are educational practices that allow students to critically evaluate, analyze, and be opened minded towards personal and global development. We have experienced different educational systems in Uganda and Ghana and a mutual experience in the ISE program at the University of Iceland. This has motivated us into scholarly discourse on the theory of critical pedagogy and collaborative learning. Based on this discourse, this project aims to understand the pedagogical practices in the educational systems of Uganda, Ghana, and the ISE programs, in relation to the theory of critical pedagogy, collaborative learning, and a reflection on our educational experiences. Appropriate literature on critical pedagogy and collaborative learning was reviewed, and the educational policies of Uganda, Ghana, and the ISEP were examined using critical pedagogy and collaborative learning lens. The study further presented the researchers' experiences under the two educational systems and the ISE program as data. The two significant findings in the discussions of this project include: The educational practices in Uganda and Ghana lack critical pedagogy and collaborative learning, despite the advocacy from the educational policies. The ISE program mainly uses critical pedagogy and collaborative learning in teaching students.